Oxygen reduction on polycrystalline palladium in acid and alkaline solutions: topographical and chemical Pd surface changes. (1st July 2015) - Srejic, I.; Rakocevic, Z.; Nenadovic, M.; Strbac, S.
Graphical abstract: Highlights: ORR on Pd(poly) was examined by RDE in acid and alkaline solutions. ORR occurs through 4e- pathway on Pd surface either oxide free or oxidized to PdOH. ORR occurs partly through 2e reduction in the potential region of PdO formation. Pd was characterized by spectroscopic ellipsometry and AFM before and after ORR. Both Pd surface roughness and the degree of its oxidation increase during ORR. Abstract: Oxygen reduction reaction (ORR) was investigated on polycrystalline palladium, Pd(poly), in acid and alkaline solutions using rotating-disc electrode technique. Pd(poly) was prepared in non-aqueous media which provided surface with good quality and reproducibility. According to cyclic voltammetry curves and to the analysis of polarization curves for ORR and of ones obtained separately for hydrogen peroxide reduction/oxidation reactions, ORR in both media proceeds mainly through 4e-series pathway in the potential regions where Pd surface is either oxide free or oxidized to PdOH. ORR occurs partly through 2e-reduction in the potential region where PdO is present on the surface. As revealed by cyclic voltammetry, spectroscopic ellipsometry and by atomic force microscopy, Pd(poly) surface undergoes both topography and chemical changes during ORR. Pd surface roughness as well as the degree of its oxidation increase during ORR.